Hubungan Kemandirian Siswa dengan Hasil Belajar Aqidah Akhlak Kelas III MI Al-Huda Citatah Cibinong Bogor - Sulis Setiawati; Moh. Romli (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This research is in the background that the third grade students of MI Al-Huda Citatah Cibinong Bogor are still not optimally managing and increasing the independence of their students in the school environment. With this background, the researcher is tasked to investigate whether there is a relationship between student independence and the learning outcomes of Aqidah Akhlak grade III MI Al-Huda Citatah Cibinong Bogor. This research was conducted at MI Al-Huda Citatah Cibinong Bogor, a research population of 71 students with a total sample of 71 people, with systematic sampling techniques from classes III A and III B. This study applied a quantitative correlation method with research instruments using a questionnaire for student independence and report card scores for the Learning Outcomes of Students' Aqidah Akhlak Akhlak. The data was analyzed using the Product Moment correlation technique. The results showed that r calculation = 0.559 > r table = 0.235. Thus, H0 was rejected and Ha was accepted, which means that there is a relationship between student independence and the learning outcomes of moral beliefs of grade III students. Similarly, the significance test with the t-test shows that t count = 5.098 > t table = 1.995. This means that the relationship between student independence and the learning outcomes of students' moral beliefs is a significant relationship. Meanwhile, the effect of the contribution of the Relationship between Student Independence and the Learning Outcomes of Students' Moral Aqidah is shown by KD (Coefficient of Determination) = 0.312 which means that the Student Independence Relationship provides 32% of the Learning Outcomes of Students' Aqidah Akhlak Akhlak.